PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PDAM BANDARMASIH KOTA BANJARMASIN - Penta Lestarini Budiati; Masrifani -; Noor Dita Meliyana (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, The purpose of this research is to determine whether the quality of service (tangibles, reliability, responsiveness, assurance, and empathy) simultaneously and partially to customer satisfaction at PDAM Bandarmasih Banjarmasin, and to know the variable quality of service (tangibles, reliability, responsiveness, assurance, and empathy) is the most dominant against customer satisfaction at PDAM Bandarmasih Banjarmasin. In this research used descriptive quantitative method. Population in this research is all customer of PDAM Bandarmasih Banjarmasin, and sample as respondent of research will be taken using Accidental Sampling technique counted 60 person that is customer which met during research. In this study the data obtained were analyzed using multiple regression analysis with SPSS program for window 16. The result of research shows that the value of F arithmetic is 142,182 bigger than the value of F table 2,546, which means simultaneously there is influence on service quality variable consisting of tangible dimension (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5), to customer satisfaction PDAM Bandarmasih Banjarmasin. Partially seen that from five dimensions of service quality there is one variable that does’t have effect on customer satisfaction PDAM Bandarmasih Banjarmasin that is assurance (X4) with value of t count equal to 1,259 smaller than t table value equal to 2,005. Furthermore, the most dominant independent variables affect the satisfaction of clean water customers in PDAM Bandarmasih Banjarmasin is the variable empathy, because it has the largest beta coefficient (0.269).